PELATIHAN PUBLIC SPEAKING BAGI SISWA SMA NEGERI 6 SEMARANG - Endang Yuliani Rahayu; Katharina Rustipa; Agnes Widyaningrum; Teguh Kasprabowo; Th. Dwiati Wismarini (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Communicative skill to convey their mind and ideas to public or also called as Public Speaking is a skill that requires many things and need to be prepared not in a short period of time. Recently more people like to learn this skill since it gives a great opportunity for society to earn a lot of money especially when more people prefer to be content creator for some social media platforms as they side job. This public service has been conducted in SMA Negri 6 Semarang for X –C graders by applying participative and collaborative approach that emphasizing on applicative and active learning. This public service has got great respons among the students.